2021
DOI: 10.1111/jpn.13647
|View full text |Cite
|
Sign up to set email alerts
|

Yucca schidigera extract decreases nitrogen emission via improving nutrient utilisation and gut barrier function in weaned piglets

Abstract: Yucca schidigera extract (YE) can decrease ammonia concentration in livestock housing, which could be associated with the inhibition of urease. The aim of this study was to investigate the other possible reasons of dietary YE supplementation reducing nitrogen emission in weaned piglets. A total of 14 crossbred weaned barrows were allotted into two groups fed the diets supplementing 0 and 120 mg/kg YE for 14 days. The YE administration decreased F/G ratio and hindgut NH3‐N production in weaned piglets (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In agreement, Fan et al [75], in weaned piglets, also reported that YSE improved feed efficiency and reduced hindgut NH3-N production with increased nutrient digestibility and reduced blood urea concentrations. Espinosa-Muñoz et al [14], in growing and finishing pigs supplemented with YSE in diets, also found decreased blood urea, triglycerides, and cholesterol.…”
Section: Effect Of Yucca Schidigera Supplementation On Production Beh...supporting
confidence: 74%
“…In agreement, Fan et al [75], in weaned piglets, also reported that YSE improved feed efficiency and reduced hindgut NH3-N production with increased nutrient digestibility and reduced blood urea concentrations. Espinosa-Muñoz et al [14], in growing and finishing pigs supplemented with YSE in diets, also found decreased blood urea, triglycerides, and cholesterol.…”
Section: Effect Of Yucca Schidigera Supplementation On Production Beh...supporting
confidence: 74%
“…It was found that YS in the broiler diets can significantly reduce the indoor ammonia concentration in poultry farms [20]. Fan et al [31] found that adding YSa to the diet reduced the nitrogen emission of piglets. Research by Patra and Yu [32] showed that QS reduced the concentration of ammonia in an in vitro rumen model, which may be due to the combination of saponins with ammonia or the reduction in the rate of ammonia release from the microbial decomposition of organic matter [33].…”
Section: Discussionmentioning
confidence: 99%
“…In traditional medicine, species of the Yucca genus have been used to treat pathologies related to inflammation, because it is rich in saponins and phenolic compounds with antioxidant effects [ 1 ]. For that reason, the dietary addition of Yucca schidigera extract (YSE) was initially used to reduce stress and improve the antioxidant capacity of broilers, swine, dairy cows, and steers [ 2 , 3 , 4 , 5 , 6 ]. In addition to antioxidant function, the saponins in YSE also have antiprotozoal activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%